Evolving Patterns of Initial RRMS Treatment in Finland (2013–2022): Insights From a Nationwide Multiple Sclerosis Register - Ahvenjärvi, Henrik; Jokinen, Elina; Viitala, Matias; Autio, Henri; Portaankorva, Anne M.; Soilu‐Hänninen, Merja; Krüger, Johanna; Ryytty, Mervi (Wiley, 2025)
Background: The treatment of relapsing-remitting multiple sclerosis (RRMS) is changing. There are limited data about initial treatment of RRMS in Finland.
Objective: Our objectives were to study the trends of initial disease-modifying treatments (DMTs) for patients with RRMS from 2013 to 2022, treatment delays, factors associated with DMT choice, DMT switch patterns, and the effect of the COVID-19 pandemic.
Methods: This retrospective register study used secondary data from the Finnish MS register. The DMTs were classified into medium-efficacy DMTs (meDMTs; beta interferons, glatiramer acetate, fumarates, and teriflunomide) and high-efficacy DMTs (heDMTs; alemtuzumab, cladribine, daclizumab, natalizumab, ocrelizumab, ofatumumab, and rituximab).
Results: The inclusion criteria were fulfilled by 2479 individuals. From 2013 to 2022, the proportion of heDMTs as the initial therapy increased by 5.3-fold from 6.9% to 43.7% (p < 0.001). Median diagnostic delay decreased from 10.1 to 4.6 months (p < 0.001). The COVID-19 pandemic did not cause treatment delays. Higher disease activity and younger age were associated with the choice of heDMT as the initial DMT. heDMTs were the preferred second DMT in patients switching due to lack of efficacy.
Conclusion: In Finland, the treatment of RRMS has shifted toward earlier diagnosis and earlier initiation of heDMTs, likely improving the prognosis of the patients.